The Role of Internal Audit Practices in Improving The Quality of Financial Reporting for Commercial Companies. A Sample of Iraqi Commercial Banks - Aqeel Abbas Hasan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to explain the role of internal audit standards in improving the quality of financial reporting for the financial reports of the banks in the research sample. Accordingly, the deductive approach was followed for the theoretical side and the inductive approach for the practical side by employing standards for internal audit standards and their role in achieving quality in financial reporting for the financial reports of the banks in the research sample. The most important conclusions were that standards standards Internal auditing has a role in achieving and improving the quality of financial reporting for the Bank of Sumer first, then the Iraqi Gulf Bank secondly, and the Assyria Bank last. The most important recommendations were to document and confirm the application of the internal audit standards for the Bank of Assyria first and the Iraqi Gulf Bank secondly by virtue of the assessments of appropriateness standards, honest representation and the appropriate timing for presenting the financial statements within Bankers' reports.